Pemikiran Islam Modern Perspektif Mustafa Kemal - Mahfud, Muhammad (Program Studi Pendidikan Agama Islam, 2020)
This paper discusses the perspective of modern Islam, Mustafa Kemal's perspective, especially the reform of Islam in Turkey. The method used in this research is library research using a qualitative approach. The analysis used to analyze the data is content analysis. The results showed that Mustafa Kemal was one of the 19th century qualified Islamic reformers. He has made a huge contribution to changing the mindset of Turkish society. By changing the old traditional order in the Ottoman Empire, and shaping it into a new face with a style of thought that actually does not change